CUSTOMARY INHERITANCE LAW OF THE SASAK TRIBE IN LOMBOK: THE POSITION OF DAUGHTERS AND THE INFLUENCE OF ADAT LEADERS - Makhrup, Abdul Gani (fakultas hukum universitas PGRI Semarang, 2025)
According to the customary law of the Sasak ethnic group in Lombok, women are traditionally excluded from inheritance rights, in line with a patrilineal system that prioritizes male lineage. However, influenced by Islamic teachings adhered to by the majority of the Sasak population, women have begun to assert their rights to inheritance, leading to disputes between male and female heirs. This study aims to examine the status of women in the Sasak customary inheritance system and the role of traditional leaders (Kepala Adat) in resolving inheritance disputes. The research employs an empirical juridical and descriptive-analytical approach. Data were collected through field interviews (primary data) and literature review (secondary data), and analyzed qualitatively. The findings indicate a shift in the position of women in Sasak customary inheritance, particularly following the Supreme Court Decision No. 179/K/Sip./1961, which affirmed equal inheritance rights for sons and daughters. Inheritance disputes are generally resolved through family deliberations, customary council meetings, or religious courts. The Kepala Adat plays multiple roles: as a mediator in family discussions, a customary judge in adat councils, and a supervisor in the execution of court decisions. This study recommends public education and socialization efforts to foster a unified understanding of women's inheritance rights, with the aim of reducing intra-family conflicts.